Komunikasi Intensif dalam Penyelenggaraan Ibadah Umrah: PT. Aina Wisata Iman Semende sebagai Kasus - Saptudin Saptudin; Muahammad Adil; K.A. Bukhori (JURNAL ILMIAH SYI'AR, 2020)
This research is based on the experience of the pilgrimage that I did in which there was a problem with the loss of pilgrims from the pilgrimage. This study aims to discuss the problems of intensive communication in the organization of Umrah. The study was conducted using qualitative methods where data was obtained based on interviews, observations, and documentation. Participants in this study were all Umrah pilgrims who served in the shade of PT. Aina Wisata Faith (AWI) Semende Travel Tour. The study was conducted using qualitative methods where data was obtained based on interviews, observations, and documentation. To analyze the data obtained from the results of the study, the authors used Miles and Huberman's Interactive Model data analysis techniques. Based on the data analysis that has been done by the author, it was found that some intensive communication was carried out, namely (1) conveying material calmly, (2) using language that was easily understood by the congregation, (3) building a pleasant atmosphere of communication, (4) using several communication media to facilitate communication so that all material is conveyed and well received by pilgrims, (5) understands the character of pilgrims to be guided, and (6) mentors are more helpful in establishing closeness with the Jammeh. And some factors influence communication, namely (1) education, (2) age, (3) gender, (4) pilgrim perception, (5) the nature or character of pilgrims, and (6) pilgrim health conditions